Hybrid energy harvester with bi-functional nano-wrinkled anti-reflective PDMS film for enhancing energies conversion from sunlight and raindrops. (December 2019) - Liu, Xiaolan; Cheng, Ke; Cui, Peng; Qi, Hui; Qin, Huaifang; Gu, Guangqin; Shang, Wanyu; Wang, Shujie; Cheng, Gang; Du, Zuliang
Abstract: The hybrid energy harvester composed of a solar cell and a water-drop triboelectric nanogenerator (WD-TENG) has been reported to harvest energy from sunlight or raindrops depends on the changing natural environment. However, the reported integrated WD-TENGs always reduce the light absorption of solar cells, resulting in a decline of solar cell efficiency. Here, a bi-functional nano-wrinkled polydimethylsiloxane (nw-PDMS) film is introduced to fabricate the hybrid energy harvester, serving as both the anti-reflective layer of the solar cell and the triboelectric layer of the WD-TENG, and simultaneously enhancing the energy harvesting efficiency from sunlight and raindrop. With significantly enhanced transmittance due to the anti-reflective coating, the power conversion efficiency of the solar cell has improved from 12.55% to 13.57%. In addition, due to the high aspect ratio, surface fluorination and strong hydrophobicity of the nw-PDMS film, both open circuit voltage ( V OC-T ) and short-circuit current ( I SC-T ) of the WD-TENG have huge enhancement by 385.5% and 299.1%, respectively. In this work, the introducing of bi-functional nw-PDMS film provides a simple and convenient strategy for designing hybrid energy harvester with enhanced output performances, which is a general route for Si-based solar cell and other kinds of solar cells. Graphical abstract: A hybrid energy harvester has been fabricated to harvest the energy of sunlight and raindrops. A bi-functional nano-wrinkled PDMS film is introduced onto the surface of the solar cell that could serve as both a triboelectric layer to collect the raindrop energy and an anti-reflective layer of the solar cell to enhance the solar energy conversion efficiency. The methodology could be easily transferred to all other type of solar cells without any barrier, showing great universality and broad application prospects. Image 1 Highlights: A bi-functional nano-winkled PDMS film is introduced to the solar cell surface as an anti-reflective coating. The anti-reflective nano-winkled PDMS film also serves as a triboelectric layer to form a WD-TENG. The energy conversion efficiency of the solar cell is enhanced from 12.55% to 13.57%. The Voc and Isc of the WD-TENG with nano-winkled structures have huge enhancement by 385.5% and 299.1%. The hybrid energy harvester could collect energies from sunlight and raindrops which enlarges its workable environments.